An extended HEART Dempster–Shafer evidence theory approach to assess human reliability for the gas freeing process on chemical tankers. (April 2022) - Sezer, Sukru Ilke; Akyuz, Emre; Arslan, Ozcan
Highlights: Human reliability analysis for the gas freeing process on chemical tanker ships. Human error assessment and reduction technique (HEART) based on modified Dempster–Shafer (D-S) evidence theory. Improving safety and human reliability on chemical tanker ships. Abstract: Human reliability assessment is vital for most critical shipboard operations such as cargo loading, discharging, purging, gas freeing, etc. on chemical tanker ships since the nature of these processes poses significant threats. There are few human reliability studies particularly applied to shipboard operations in the maritime industry. To remedy this gap, the paper assesses human reliability systematically during the gas freeing process on a chemical tanker ship. To achieve this purpose, an extended HEART d -S (Dempster–Shafer) evidence theory approach is utilised. Although HEART (Human Error Assessment and Reduction Technique) presents a practical human reliability assessment tool, it heavily relies on the judgment of a single rater during APOE (assess proportion of effect). The paper adopts d -S evidence theory to remedy the aforementioned gap since it fuses raters' opinions. The first novelty of the proposed hybrid method is the use of customized task analysis for shipboard applications within a second-generation HEART d -S evidence method in the maritime industry. Besides its theoretical background, the paper provides practical contributions to maritime safety professionals, chemical tanker ship owners, and safety inspectors to enhance their operational safety and to minimize the probability of human error during the gas freeing process on board chemical tanker ships.